Die Quench Process Sensitivity of AA7050. (November 2019) - Boulis, R.; DiCecco, S.; Worswick, M.J.
Abstract: The current work investigates the sensitivity of AA7050 aluminum alloy sheet to the thermal cycle involved in the die quenching (DQ) process. This entailed the variation of three key parameters in the thermal cycle, namely solutionizing time, transfer time and quench rate, considering both water quenching (WQ) and die quenching (DQ) at various die pressures. Following a lab-grade T6 heat treatment, Vickers hardness (HV-1000) measurements of all test conditions and tensile testing on a reduced number of test conditions were completed. The results showed only limited sensitivity to solutionizing time for the range of conditions tested. Longer transfer times and slower cooling rates both negatively affected final hardness properties, with up to 4% reduction in final hardness relative to the water-quenched T6 condition. Higher cooling rates during die-quenching produced statistically similar final tensile properties to those achieved from water quenching, following a T6 heat-treatment; while slower cooling rates resulted in significant reductions in tensile strength and uniform elongation. Limiting dome height testing of a 101.6 mm dome sample under die-quench conditions produced a major true limit strain of 0.42. The die-quench limit strain compared favourably against the limit strains of the same geometry in the T6 condition at room temperature and 150 °C (isothermal), which were 0.12 and 0.18, respectively.